Village Government Strategy in Building Public Service Motivation: A Systematic Review of Philosophical Perspectives and Public Administration Theory - Yusup Musyaffa; Mulyaningsih; Aip Zaenal Muttaqin; Hasyim Burhani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Village governments play a strategic role as the frontline of public service delivery; however, numerous studies indicate that the quality of public services at the village level continues to face fundamental challenges, particularly concerning the motivation of public officials. This research endeavors to rigorously analyze the strategic approaches employed by village governments in promoting Public Service Motivation (PSM) through the lenses of philosophical inquiry and public administration theory. The investigation utilizes a systematic literature review methodology, scrutinizing pertinent academic works pertaining to PSM, village governance, the philosophy of public service, and theoretical frameworks in public administration. The data were examined through thematic and narrative synthesis methodologies to discern patterns, trends, and existing gaps in the scholarly literature. The outcomes indicate that PSM has yet to be established as a fundamental analytical construct in the realm of village governance research, but instead emerges implicitly within dialogues surrounding governance, principles of good governance, and institutional enhancement.. The literature predominantly emphasizes structural and procedural approaches, while the motivational dimension of village officials remains underexplored. Furthermore, this review finds that philosophical foundations of public service and local wisdom play a crucial role in shaping the service orientation of village officials, yet these dimensions have not been systematically integrated into the PSM framework. This research asserts that the promotion of Public Service Motivation (PSM) within rural governmental entities necessitates a comprehensive strategy that incorporates structural, theoretical, and philosophical aspects. This investigation advances the discipline of public administration by broadening the discussion on PSM to encompass the realm of village governance, in addition to establishing a conceptual framework for subsequent scholarly inquiry and policy formulation. Keywords: Public Service Motivation, Public Administration, Public Service Philosophy, Systematic Literature Review, Village Government.